The pedagogy of watching Shakespeare - Marshall, Bethan 1958-; Edwards, Myfanwy; Dixie, Charlotte (Cambridge University Press, 2024)
The pedagogy of acting out Shakespeare has been extensive. Less work has been done on how students learn through spectatorship. This element will consider all within the current context of Shakespeare teaching in schools. Using grounded research, it will include work undertaken on a schools National Theatre production of Macbeth, as well as classroom-based, action research, using a variety of digital performances of Shakespeare plays. Both find means of extending student knowledge in unexpected ways through encountering interpretations of Shakespeare that the students had not considered. In reflecting on the practice of watching Shakespeare in an educational context- both at the theatre and in the classroom- this Element hopes to offer suggestions for how teachers might re-think the ways in which they present Shakespeare performed to their students particularly as a powerful way of building personal and critical responses to the plays
Title from publisher's bibliographic system (viewed on 18 Apr 2024)
Keywords: Shakespeare, William / 1564-1616 / Study and teaching / Great Britain; Shakespeare, William / 1564-1616 / Dramatic production / Great Britain; Shakespeare, William / 1564-1616 / Stage history / Great Britain; Drama in education; Theater / Study and teaching / Great Britain; Drama / Study and teaching / Great Britain